Two new species of Austrotinodes Schmid (Insecta, Trichoptera, Ecnomidae) from southeastern Brazil - Cavalcante, Bruna Maria Da Silva; Dumas, Leandro Lourenço; Nessimian, Jorge Luiz (Zootaxa, 2017)
The genus Austrotinodes Schmid, with 55 species described from the New World and Australia, is the second largest genus of the family Ecnomidae. Herein, we describe and figure two new species of Austrotinodes from Parque Nacional da Tijuca, Rio de Janeiro state, southeastern Brazil: A. carioca sp. nov. and A. quintarellii sp. nov.